2001
DOI: 10.1159/000046526
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Evaluation of Patients with Beta-Thalassemia major

Abstract: Abnormalities in the immune system and zinc homeostasis in patients with β-thalassemia major (TM) have been reported. Since zinc ion is essential for the efficiency of the immune system and is required to induce biological activity to thymulin (Zn-FTS), a biochemically defined thymic hormone, we investigated the plasma levels of zinc and both active thymulin (Zn-FTS) and total zinc saturable thymulin (Zn-FTS+FTS) in 18 patients with TM aged between 2 and 31 years and 22 normal controls of the same age. Inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
1
24
1
1
Order By: Relevance
“…While this outcome has been reported previously (Dwyer et al, 1987;Lombardi et al, 1994), contrasting findings of higher CD8, reduced CD4 and decreased CD4/CD8 ratio were also reported (Umiel et al, 1984;Grady et al, 1985;Ezner et al, 2002). Few studies even reported thalassemia patients with low CD8 percentage (Cunningham-Rundles et al, 2000;Consolini et al, 2001). A study conducted by Cruz et al (2006) reported a negative correlation between CD8+ T-lymphocytes and iron stores in HFE homozygous hemochromatosis male patients; this correlation was not found in our patient population.…”
Section: Discussioncontrasting
confidence: 58%
“…While this outcome has been reported previously (Dwyer et al, 1987;Lombardi et al, 1994), contrasting findings of higher CD8, reduced CD4 and decreased CD4/CD8 ratio were also reported (Umiel et al, 1984;Grady et al, 1985;Ezner et al, 2002). Few studies even reported thalassemia patients with low CD8 percentage (Cunningham-Rundles et al, 2000;Consolini et al, 2001). A study conducted by Cruz et al (2006) reported a negative correlation between CD8+ T-lymphocytes and iron stores in HFE homozygous hemochromatosis male patients; this correlation was not found in our patient population.…”
Section: Discussioncontrasting
confidence: 58%
“…In another study, Kwan shows that while serum zinc level decreases and serum zinc binding capacity (ZnBC) increases in nutritional zinc deficiency, in thalassemic patients serum zinc level decreases but ZnBC does not increase simultaneously [22]. Though there are wide variations in different reports, these discrepancies can be attributed to differences in patients' ages, rather than to difference in treatment protocols, including differing transfusion rates or chelation therapies [22][23][24][25][26][27]. Some reports indicate that desferrioxamine increases urinary zinc excretion and may decrease zinc body content [8,9,28].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this low activity can be Zn insufficiency, an essential element required for function of immune cells (29,30). In fact, in used iron chelators in TM, Desferoxamine (DFO), Deferiprone (DFP), and Deferasirox (DFX), all have been shown to lead to Zn deficiency (31).…”
Section: Functional Alternationsmentioning
confidence: 99%